2022
DOI: 10.3233/hab-220006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of some hematological parameters between male and female patients infected with COVID-19

Abstract: BACKGROUND: COVID-19 is a highly contagious virus that is rapidly spreading across the world. As the number of COVID-19 patients is quickly rising, and certain nations and areas, such as the third world countries, lack the medical resources, it is critical to track and monitor a patient’s status using blood parameters on regular testing. The aim of this study is to compare the serum D-dimer levels, Ferritin, CRP, WBCs, Lymphocytes, and Neutrophils in male and female patients infected with COVID-19. OBJECTIVE A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Despite the unchanged MO count, monocyte distribution width (MDW) was shown to increase in the patients and suggested to be a diagnostic tool in COVID-19 [26]. Leucopenia was also shown to develop in some COVID-19 patients and suggested that WBC count may provide some information about the severity of the cases [27]. Absence of comparison between healthy and COVID-19 infected patients is the limitations of the study.…”
Section: Discussionmentioning
confidence: 85%
“…Despite the unchanged MO count, monocyte distribution width (MDW) was shown to increase in the patients and suggested to be a diagnostic tool in COVID-19 [26]. Leucopenia was also shown to develop in some COVID-19 patients and suggested that WBC count may provide some information about the severity of the cases [27]. Absence of comparison between healthy and COVID-19 infected patients is the limitations of the study.…”
Section: Discussionmentioning
confidence: 85%
“…Venous blood samples of up to 5 ml were taken from the vein by using a 5 ml syringe. The samples were kept for 30 minutes at room temperature and then the tubes were transported to centrifugation at 1800 rpm for twenty minutes at room temperature [15]. Serum was kept in separate tubes under frozen conditions until the samples were used for albumin and C-reactive protein tests.…”
Section: Specimen Collectionmentioning
confidence: 99%